Preliminary results from measurements of far infrared radiation (80-600 cm-1) taken during the european aqua thermodynamic experiment (EAQUATE) campaign, 13-23 september 2004. - Cox,C; Murray,J; Green,PD; Harries,JE; Pickering,J; Taylor,JP (2005)
During a recent flight campaign, measurements of far infrared radiation were taken with a Fourier transform spectrometer. The results taken in clear sky conditions will further our understanding the atmosphere and our ability to predict the climate. © 2005 Optical Society of America.